Repurchase Intention: Peran Brand Image, Brand Heritage, dan Brand Love - Suryana Hendrawan; Muhammad Ali Fikri; Adelia Dwi Nurisaputri (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2026)
Brand image and brand heritage shape repurchase behaviour through consumers' emotional attachment to the brand. However, empirical studies that simultaneously examine the roles of brand image and brand heritage in shaping repurchase intention through brand love in the automotive sector of emerging markets, particularly Indonesia, remain limited. This study aims to analyse the influence of brand image and brand heritage on repurchase intention with brand love as a mediating variable. The study sample consisted of 103 respondents selected using purposive sampling among Honda users in the Special Region of Yogyakarta. Data were collected using a Likert-scale questionnaire and analysed with PLS-SEM. The research findings indicate that Honda’s brand image and brand heritage are associated with stronger levels of brand love, as well as a higher likelihood that consumers will choose Honda again for their next purchase. Brand image and brand heritage are not only directly related to repurchase intentions but also indirectly influence these intentions through brand love, which acts as an emotional bridge between consumers' perceptions of the brand and their repurchase decisions.Overall, all proposed hypotheses—including the direct relationship between brand image and brand heritage with brand love and repurchase intention, as well as the mediating role of brand love are supported by the data, thereby underscoring the importance of managing both current brand performance and the brand’s historical identity to sustain repurchase behavior in the competitive automotive market.